Pengaruh Aktivitas Bermain Dakon Terhadap Kemampuan Ketangkasan Tangan Pasien Cedera Tangan - Aniek Puspitosari; Vincentia Nindya Christy (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Hand injury is all kinds of trauma caused by various mechanisms that occur in the hand and can cause injury to the hand structure. One result of a hand injury is a decrease in hand dexterity. Dexterity is the speed of the hand to take or capture and place objects from one place to another so that it has an important role in daily activities. Dakon is one of the activities that can be chosen as a hand dexterity exercise. The purpose of this study was to determine the effect of dakon playing activities on the hnad dexterity abilities of patients with hnad injuries. Methods: Quantitative research using quasi experimental design. Sampling using purposive sampling technique. Data analysis using statistical tests paired sample t-test. Results: showed a significant increase in hand dexterity with a significant level of ρ <0.05. In the right hand the results were 0.012 <0.05, left hand 0.000 <0.05, right hand + left + second hand 0.001 <0.05 and on assembly subtest 0.014 <0.05. Conclusion: Of the study showed that playing dakon activity can improve the dexterity of the hand injured patient's hand.